Effects of Exposure to the Hormone Cortisol in Pregnant Women on Body Weight and Length at Birth of Babies: A Prospective Study - Sudirman, Jumrah; Sampara, Nurqalbi; Muzakkir, Muzakkir; K, Hairuddin; Darmiati, Darmiati; K, Rahayu Eryanti; Anwar, Khalidatul Khair; Saleng, Hasriani (Jurnal Kesehatan Masyarakat, 2024)
Other mental disorders with a reasonably high prevalence are pregnancy stress of 92.8% and anxiety of 32.6%. Pregnancy pressure can potentially cause low birth weight and small head circumference. In addition, stress during pregnancy will affect neurobehavioral development, ACTH, cortisol, norepinephrine, and epinephrine levels in neonates. This study aims to assess cortisol exposure in pregnancy with birth weight and birth length in infants. This study uses a cohort study approach. The sample in this study was the third-trimester pregnant women many as 152 respondents. The research instrument used checklist sheets and laboratory tests using the ELISA method. The resulting data were processed using the unpaired t-test and the Pearson correlation test. The results showed a correlation between cortisol levels and birth weight with a value of p = 0.004 0.05 and a value of r = -0.230, indicating that both variables had a low correlation and a negative relationship. This means the higher the cortisol level, the lower the baby's birth weight. There is a correlation between cortisol levels and the baby's birth length with a value of p = 0.003 0.05 and r = -0.239, showing that both variables have a low correlation and a negative relationship. The higher the cortisol level, the shorter the baby's birth length. Maintaining the mental health of pregnant women, primarily through family support and health workers, is essential to avoid excessive stress and depression during pregnancy.